No effect of the α1-antichymotrypsin A allele in Alzheimer's disease. Issue 1 (1st July 1997) - Didierjean, O; Martinez, M; Campion, D; Hannequin, D; Dubois, B; Martin, C; Puel, M; Anterion, C Thomas; Pasquier, F; Moreau, O; Babron, M C; Penet, C; et al.
Abstract : The apolipoprotein E (ApoE)-ε4 allele is associated in a dose dependent manner to an increased risk for Alzheimer's disease. However, the ApoE-ε4 allele effect does not account for all patients with Alzheimer's disease, and the existence of other genetic risk factors has been postulated. Kamboh et al reported an association between Alzheimer's disease and the A allele of α1-antichymotrypsin (Aact) gene, which was not confirmed in a larger series more recently analysed. The ApoE and Aact genotypes were analysed in 314 patients with Alzheimer's disease and 173 healthy controls, confirming the dose dependent effect of the ApoE-ε4 allele. Nevertheless, even using odds ratios adjusted for age and sex, there was no significant effect of the Aact genotype on Alzheimer's disease or on the ApoE-ε4 allele associated risk for Alzheimer's disease.